2016
DOI: 10.1002/2016gl070621
|View full text |Cite
|
Sign up to set email alerts
|

Identifying errors in dust models from data assimilation

Abstract: Airborne mineral dust is an important component of the Earth system and is increasingly predicted prognostically in weather and climate models. The recent development of data assimilation for remotely sensed aerosol optical depths (AODs) into models offers a new opportunity to better understand the characteristics and sources of model error. Here we examine assimilation increments from Moderate Resolution Imaging Spectroradiometer AODs over northern Africa in the Met Office global forecast model. The model und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 80 publications
4
25
0
Order By: Relevance
“…The use of soil moisture in the model 10 is also implicated, since the model uses soil moisture over a 10cm layer, whereas in reality it is the skin soil moisture that is relevant and both the soil makeup (sandy soils) and the hot, dry conditions in the northern Sahel and Sahara mean that the actual time between rainfall and dust emission can be much shorter than that predicted by the SWAMMA simulations (Gillette et al, 2001, Bergametti et al, 2016. This role of the land-surface errors in the Sahel is consistent with recent analysis of operational global UM runs (Pope et al, 2016). Finally, clay fraction is a crucial soil texture parameter in several of the dust 15 emission and flux calculations and high clay fractions over the west coast in combination with strong northerly winds blowing off the Atlantic cause high AOD values there which are not seen in observations.…”
Section: Discussionsupporting
confidence: 72%
“…The use of soil moisture in the model 10 is also implicated, since the model uses soil moisture over a 10cm layer, whereas in reality it is the skin soil moisture that is relevant and both the soil makeup (sandy soils) and the hot, dry conditions in the northern Sahel and Sahara mean that the actual time between rainfall and dust emission can be much shorter than that predicted by the SWAMMA simulations (Gillette et al, 2001, Bergametti et al, 2016. This role of the land-surface errors in the Sahel is consistent with recent analysis of operational global UM runs (Pope et al, 2016). Finally, clay fraction is a crucial soil texture parameter in several of the dust 15 emission and flux calculations and high clay fractions over the west coast in combination with strong northerly winds blowing off the Atlantic cause high AOD values there which are not seen in observations.…”
Section: Discussionsupporting
confidence: 72%
“…Measurements should include the following: mass concentrations of chemical components (soot, organics, ammonia, sulfate, nitrate, mineral dust, and sea salt), number concentrations (of PM 1 , PM 2.5 , and PM 10 ), and size distribution (if possible resolved by chemical species). Evaluating whether relevant emissions and feedback processes are treated accurately by a model is challenging, although data assimilation can provide valuable information (Pope et al, 2016). In addition to key meteorological parameters associated with aerosol emissions (e.g., surface winds and soil moisture), the effects of aerosols on radiation and clouds, for example, depend on the physical and chemical properties of the aerosols.…”
Section: User Requirements For Benchmark Testingmentioning
confidence: 99%
“…For example, through analysis of rain and lightning observations, Pope et al . [] concluded that “ haboobs (cold pool outflows from moist convection) are an important dust source in reality but are badly handled by the model's convection scheme .” Heinold et al . [] made simulations over West Africa with 40, 12, and 4 km grid spacing.…”
Section: Introductionmentioning
confidence: 99%